Color Variation in 3D-Printed Orthodontic Aligners as a Compliance Indicator: A Prospective Pilot Study - Francesca Cremonini; Giuseppe Chiusolo; Filippo Pepe; Luca Lombardo (Applied Sciences, 2025)
Patient compliance remains a significant challenge in orthodontic treatment with clear aligners, as adherence to prescribed wear time is often suboptimal. This study investigated the potential of colorimetric analysis as a method to assess compliance with NOXI 3D-printed night-time aligners. Specifically, it evaluated color variations in polyamide aligners due to thermo-oxidation, using the RGB (Red, Green, Blue) color model as a non-invasive indicator. In total, 10 patients participated in this prospective study, wearing aligners for either 7 or 12 h daily over a 14-day period. Colorimetric measurements were collected via a smartphone-based application, and statistical analyses examined correlations between wear duration and color changes. The results revealed a significant association between a longer wear time and increased discoloration (p < 0.001), supporting the feasibility of RGB-based monitoring as a reliable compliance tool. However, individual variability in saliva composition, diet, and oral hygiene may have influenced the results, highlighting the need for further research into potential confounding variables. These findings underscore the promise of integrating digital monitoring technologies to improve adherence tracking and patient management in orthodontics. Future studies should refine the methodology and validate its efficacy in larger, more diverse populations.